Pengaruh Kualitas Produk, Harga, dan Citra Merek terhadap Loyalitas Pelanggan Kosmetik Natural Nusantara di Gunungkidul - Anik Rini Astuti; Eka Sudarusman (Telaah Bisnis, 2021)
The purpose of this study was to determine the effect of Product Quality, Price, and Brand Image on Customer Loyalty (Study on Customers of Natural Nusantara Cosmetics Product Users in Gunungkidul). The sampling technique has used a Non-Probability model used was the purposive sampling method. The sampling criteria in this study were that some customers of Natural Nusantara cosmetics users in Gunungkidul, had purchased Natural Nusantara cosmetic products at least twice. The sample in this study were 100 respondents, The data analysis method used Multiple Regression, Y = 15.163 + 0.212X1 + 0.433X2 + (-0.006X3). The results showed that product quality and price had a positive and significant effects on customer loyalty of Nusantara Natural Cosmetics users in Gunungkidul, so H1 and H2 was accepted. While brand image had a negative and had no significant effect on customer loyalty of users of Natural Nusantara Cosmetics products in Gunungkidul, so H3 is rejected.